Urban segregation and school backwardness in Rio de Janeiro - Fátima Alves; Creso Franco; Luiz César de Queiroz Ribeiro (CEPAL Review, 2008)
This article analyses a dimension that is almost completely absent from studies on the socio-territorial mechanisms that reproduce inequalities in Brazil: differences in the risk of school backwardness among children and young people between 7 and 17 years of age, based on residential segregation in Rio de Janeiro. Data from the 2000 Population Census were used to construct two sets of multilevel logistic regression models to quantify the risk of school backwardness among primary school students in fourth and eighth grade, according to individual characteristics, family socioeducational conditions and the social setting of their place of residence. Apart from showing that residence in a ghetto (favela) is associated with a higher risk of school backwardness, the results show that the risk of backwardness and school dropout is higher among inhabitants of favelas located in wealthy neighbourhoods. Possible explanatory mechanisms for these findings are reviewed.